The effectiveness of the combination of podcast and two stay two stray in teaching listening - Nisa, Tifani Diah; Candraloka, Olyvia Revalita (Universitas Muhammadiyah Malang, 2024)
This study aims to find out the effectiveness of the combination of Podcast and Two Stay Two Stray in teaching listening. The true experimental design with a pretest-posttest control group design was used in this study. The research population consisted of eleventh grade students from SMAN 1 Tahunan. The research sample consisted of classes XI-6 and XI-11, where XI-6 was assigned as the control group whereas XI-11 as the experimental group. It was chosen using a straightforward random sampling method. The instrument used by researchers to assess students' listening skills was providing 25 multiple-choice listening questions. The results demonstrated that the mean scores for both groups before and after the exam differed significantly. Furthermore, the analysis results utilizing the independent sample t-test showed that the t-test score (14.72>1.695) was higher than the t-table score. It indicates that the alternative hypothesis was accepted. Referring of the study’s findings, it can be concluded that the combination of Podcast and Two Stay Two Stray can improve students’ listening skill.